THE SCHOLARLY LEGACY OF B.KH. KARMYSHEVA AND THE PROBLEMS OF ETHNOGENESIS IN CENTRAL ASIA - Sherzod Turaev (Scholar Express Journal, 2025)
Historical research indicates that Central Asia has long been a region inhabited and utilized by both nomadic and sedentary population groups. These ethnic communities developed through mutual interaction, cultural exchange, and integration. The unique cultural heritage they created has significantly contributed not only to the development of the region but also to the broader progress of world civilization. The origins and formation of ethnic groups that emerged in the Eurasian space during the medieval period and later became part of modern national structures remain complex scholarly issues. This is primarily due to the limited availability of source materials and the insufficient development of theoretical frameworks. A prominent scholar who introduced innovative approaches in this field and made a substantial contribution to the in-depth study of Central Asian ethnic history was B.Kh. Karmysheva. Her scholarly work has served as an important methodological foundation for subsequent researchers
Keywords: Central Asia; B.Kh. Karmysheva; problems of ethnogenesis; karakalpaks